Symptomatic ovarian involvement as the initial presentation of primary mediastinal large b-cell lymphoma - Alexia Piperidou; Ioannis Drandakis; Maria-Aikaterini Lefaki; Eleftheria Lakiotaki; Helen Plyta; Georgia Sypsa; Maria Tsolakou-Dalekou; Maria Androulaki; Fotios Panitsas; Eleni Plata; Penelope Korkolopoulou; Theodoros P. Vassilakopoulos (Elsevier, 2022)
Primary mediastinal large B- cell lymphoma (PMLBCL) is a mature aggressive B-cell lymphoma which affects mainly young and middle-aged women. The majority of patients present with bulky mediastinal lymphadenopathy. Extranodal involvement is a rare phenomenon at disease presentation. Herein, we describe a case of a young female with PMLBCL presenting with symptomatic, bulky ovarian involvement. The 23-year old patient presented at the Emergency Department with abdominal pain. The chest X-ray film revealed a mediastinal mass and CT scan revealed a large pelvic mass, possibly involving the ovaries. Due to the development of signs of acute abdomen, she was urgently transferred to the operation room where surgical resection of the right ovary and the adjacent mass was performed. The histological examination of the resected material revealed proliferation of PMLBCL cells. This is the first report in the scientific literature describing symptomatic ovarian mass as the initial mode of presentation of PMLBCL.